Prevalence of nonsyndromic oral clefts in a reference hospital in the state of Minas Gerais, Brazil, between 2000-2005 Prevalência de fissuras orais não-sindrômicas em um hospital de referência no estado de Minas Gerais, Brasil, entre 2000 e 2005 - Hercílio Martelli-Junior; Letícia Vieto Porto; Daniella Reis Barbosa Martelli; Paulo Rogério Ferreti Bonan; Amanda Beatriz Freitas; Ricardo Della Coletta (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The aim of the present study was to analyze the prevalence of nonsyndromic oral clefts in children receiving treatment at the Center for the Rehabilitation of Craniofacial Anomalies, José do Rosário Vellano University, Alfenas, MG, Brazil. All the data for the epidemiological study was retrieved from the files of 126 pediatric patients with oral clefts without any additional malformation, who came to the center for treatment between 2000 and 2005. A predominance of clefts was observed in Caucasians, and the ratio of male to female was 1.3. Males were 2.57 times more affected by cleft lip and palate (CLP) than females. CLP with a prevalence of 39.68% and isolated cleft lip (CL) with a prevalence of 38.09% were the most common anomalies, followed by isolated cleft palate (CP; 22.23%). Complete and unilateral CLP (26.19%) presented the highest prevalence, followed by incomplete and unilateral CL (23.81%). The present study presents the experience of a reference hospital in the state of Minas Gerais; however, the real prevalence of oral clefts in Brazil is still unknown. Our findings differ from those of a few previous Brazilian reports because they suggest similar prevalences of CLP and CL, and a higher prevalence of CLP in Caucasian males. O objetivo do presente estudo foi analisar a prevalência de fissuras orais não-sindrômicas em crianças que receberam tratamento no Centro de Reabilitação de Anomalias Craniofaciais da Universidade José do Rosário Vellano, Alfenas, MG, Brasil. Todos os dados epidemiológicos deste estudo foram obtidos dos arquivos de 126 pacientes pediátricos com fissuras orais sem outra malformação adicional que compareceram ao Centro para tratamento entre 2000 e 2005. O predomínio das fissuras foi observado em caucasianos e a relação entre homens e mulheres foi de 1,3. Os homens foram 2,57 vezes mais atingidos por fissuras lábio-palatais (FLP) do que as mulheres. FLP com prevalência de 39,68% e fissuras labial isolada (FL) com prevalência de 38,09% foram as anomalias mais comuns, seguidas por fissuras palatinas isoladas (FP, 22,23%). As FLP completas e unilaterais (26,19%) foram as de maior prevalência, seguidas por FL incompletas e unilaterais (23,81%). O presente estudo mostrou a experiência de um Hospital de Referência em Minas Gerais; contudo, a verdadeira prevalência de fendas orais ainda é desconhecida. Nossos achados divergem dos de alguns poucos estudos anteriores por demonstrar prevalências similares de FLP e FL, e um acometimento maior de FLP em caucasianos do sexo masculino.